Analysis of Actor Dynamics Within the Institutional Framework of Public Private Partnership in Street Lighting in Denpasar City - Indika Sekar Pratiwi; Amrita Nugraheni Saraswaty (Green Publisher Indonesia, 2026)
Delays in Public-Private Partnership (PPP) projects are often attributed to financial constraints or technical challenges, while institutional dynamics and actor interactions remain underexplored, particularly at the local government level. This study aims to analyze actor dynamics within the institutional framework of the Street Lighting PPP project in Denpasar City, Indonesia. A case study approach was employed by integrating MICMAC structural analysis and MACTOR actor analysis to identify key variables, map influence structures, and examine actors' strategic positions toward project objectives. The findings reveal that regulatory change functions as an external structural shock that restructures inter-actor relationships and increases coordination complexity. The actor structure demonstrates a pattern of mutual interdependence, where highly influential actors simultaneously exhibit high dependence. This configuration produces a collective yet defensive decision-making mechanism, as actors tend to minimize institutional risk and individual accountability. Consequently, project delays cannot be understood solely as technical or financial issues, but rather as outcomes of relational configurations requiring collective legitimacy before strategic decisions are made. This study highlights the importance of incorporating actor dynamics analysis as a diagnostic tool in PPP preparation stages to strengthen coordination, align regulatory interpretation, and enhance implementation certainty.